(untitled) (Research, Society and Development, 2022)
The objective of this study is to describe the actions of health professionals and students in the school environment, prioritizing the nurse as a protagonist of health education in a preventive way with emphasis on first aid. This is an integrative review, in which the theoretical framework was developed through research in electronic databases: Virtual Health Library (VHL) and the following databases: National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO) and electronic scientific journals. In the periods 2015-2021. It was possible to show how the performance of nursing in the school environment for the promotion of first aid knowledge is vital to avoid alarming outcomes in situations of imminent risk. Many times, the lay public is the first to show these cases, meanwhile, the education of this public in first aid since the school phase is essential so that this child, when becoming an adult, knows the basic conducts of basic life support and is able to provide a more qualified assistance. After analyzing all the factors that make up this study, we can conclude that the presence of a health professional, particularly a nurse, within the school environment as an educator and promoter of health, the school in turn, is responsible for training and building the citizens of our society, thus making it necessary to introduce a basic life support training plan, to influence the migration of curative culture to a more preventive culture.